Karakteristik Fluida Panas Bumi Menggunakan Geoindikator Cl-Li-B di Daerah Desa Bakan - Musa Salvador Arikalang; Rolles Nixon Palilingan; Jeferson Polii (Jurnal FisTa : Fisika dan Terapannya, 2022)
Geothermal is a natural heat resource that comes from the interaction between hot rock and water. The results of these interactions are trapped in a place called a geothermal reservoir. North Sulawesi is an area that has geothermal potential, one of which is in Bakan, Bolaang Mongondow, geothermal potential here is a manifestation of hot springs. The purpose of this study was to determine the characteristics of geothermal fluids in the Bakan Village area, using the Cl-Li-B geoindicator method. The use of the Cl-Li-B geoindicator results in Cl being more dominant than Li and B indicating that hot water coming from a heat source that rises to the surface is a fluid originating from a heat source with little cooling, a low B/Li ratio indicates that the fluid zoning is in the upflow zone.